Identification of Novel Compound Heterozygous Mutations in the GAN Gene of a Chinese Patient Diagnosed With Giant Axonal Neuropathy - Xu, Xiaomin; Yang, Xiaokai; Su, Zhongliang; Wang, Hai; Li, Xiaoqing; Sun, Congcong; Wang, Wenhuan; Chen, Yao; Zhang, Chenhui; Zhang, Hongping; Jin, Fan; Zheng, Jiayong (Frontiers in Neuroscience, 2020)
Giant axonal neuropathy (GAN) is a very rare autosomal recessive disorder characterized by abnormally large and dysfunctional neuronal axons. Mutations in the GAN gene have been identified as the cause of this disorder. In this report, we performed a detailed phenotypic assessment of a Chinese patient with GAN. An array-based exon capture test and targeted next-generation sequencing were used to detect the suspected mutation sites. Compound heterozygous mutations of p.S79L (c.236C>T) in the BTB domain and p.T489S (c.1466C>G) in the kelch domain were identified in the proband’s genome. S79L was a known mutation, and T489S was reported for the first time. The p.S79L and p.T489S were confirmed in the proband’s mother and father respectively. Both mutations were located in highly conserved regions, and affected the predicted protein crystal structures. The proband’s sural biopsy revealed the classical GAN phenotype of swollen axons filled with closely packed neurofilaments. The combined application of the next-generation sequencing platform and bioinformatics analyses was effective methods for diagnosing GAN. The novel compound mutations of S79L and T489S in the GAN gene were likely the cause of the patient’s GAN symptoms. Our findings enrich the spectrum of mutations associated with this rare type of axonopathy.